Physical activity and perceived health among adolescents in Troms. Data based on Fit Futures - a health survey among adolescents - Tennebø, Kjetil (Universitetet i Tromsø, 2013)
Background: Perceived health is a predictor of morbidity and mortality in adults and has been an important measure of the general health status in population health studies for decades. Thus, perceived health during adolescence should be of high interest from a Public Health perspective. The aim of this thesis was to investigate the association between leisure time physical activity and perceived health among 15-18 year old adolescents in the municipalities of Tromsø and Balsfjord, Norway. Material and methods: Data is provided from Fit Futures (2010-2011), part of the Tromsø Study. Participation rate was 92%. The material consisted of 914 students aged 15-18 years (Mean 16.1, ±0.49), of whom 48.2% were girls. Results: A significant positive association between leisure time physical activity and perceived health was found for both boys and girls. Compared with being sedentary, boys had an odds ratio of 5.4 (p<0.001) in favor of perceiving health as good if being very active. For girls, the odds ratio in favor of perceiving health as good was 5.9 (p<0.01) for those who were very active, compared with being sedentary. Conclusion: For both boys and girls, perceived health seems to improve with increasing amount of leisure time physical activity. The most active adolescents perceived their health significantly better than their less active peers.